Mapping wine tourism: A systematic literature review - Pé-Curto, A.; Loureiro, S. M. C.; Guerreiro, J. (14th Annual Conference of the EuroMed Academy of Business: Contemporary Business Concepts and Strategies in the new Era, 2021)
This research makes an overview of the current scientific state of the art about Wine Tourism (WT). For this purpose, a systematic review of literature (Loureiro et al., 2020; Tranfield et al., 2003) was conducted to map wine tourism. The systematic analysis uses the main research articles published in the most relevant journals since 1997 (the first indexed studies were published in this year). The current study explored the objective/goals, methodologies, theories, constructs, moderators, mediators, antecedents, consequences, main conclusions and gaps, as well other relevant aspects of the research. A total of 2039 papers were collected from Web of Science (WoS) and 2178 papers were extracted from Scopus. First, duplications were removed, second for quality assessment, we matched each paper with the Academic Journal Guide 2018 from the Chartered Association of Business Schools (ABS) ranking so that only papers featuring in ABS 4, ABS3 and ABS2 were considered, 366 resulted Through abstract reading 234 papers were excluded. Additionally, from the initial literature review we found several papers being often cited, but not included in the selected 132 papers neither above ABS1. Most of those papers (30) with significant citations were from wine sector journals and, therefore, were included in the systematic review, which end up with a total of 162 papers to analyze (figure 1). From 1997 to 2010, a total of 44 articles were published in the following journals: Journal of Travel and Tourism Marketing, Recreation Research, International Journal of Contemporary Hospitality Management, International Journal of Tourism Research, International Journal of Wine Business Research, Journal of Wine Research. Such studies were responsible for 57% of the articles published. From 2011 onwards the articles published more than doubled the previous period. From the 118 articles published after 2011, 58% were published on the following journals: Current Issues in Tourism; International Journal of Wine Business Research, Tourism Analysis, International Journal of Contemporary Hospitality Management, International Journal of Tourism Research, Tourism Management, Tourism Recreation Research, Journal of Hospitality and Tourism Research, Tourism Planning and Development. Wine tourism sector has been studied using 38 different theories identified in the articles analyzed. Only 9 theories (51.9% of the total cited theories) are cited more than on time. The main theories cited in the papers include Servicescape (Bitner, 1992; Williams, 2021), Consumer behaviour (Loureiro et al., 2021; Schiffman et al., 2001), Experience economy (Pine and Gilmore, 1998; Vo Thanh and Kirova, 2018) Destination choice (Loureiro, 2020; Wu and Liang, 2020) and Theory of planned behaviour (TPB) (Ajzen, 1988, 2020; Sussman and Gifford, 2019). The articles published during the period of analysis on this topic are mostly based on empirical findings (92%), while 8% the articles analyzed are theoretical, and 16.1% are qualitative. The most common used data collection technique is the survey method. The systematic literature analysis also identified the principal constructs used in this research area. The most frequent antecedents of Loyalty are Involvement (12%) immediately followed by Experience (11%). Some other constructs observed are Perceived value (6%), Motivation (6%), Destination image (5%), Satisfaction (4%), Authenticity (3%), Quality (2%), Trust (2%), Service (2%) and Personal Attributes (2%). These 11 constructs represent a concentration of 55% within the antecedent’s constructs. Within the mediators and moderators, the most frequent used constructs we observe being mentioned in the literature were Satisfaction (13.7%), Involvement (12.3%), Winescape (8.2%), Intention to revisit (5.5%), Loyalty (4.1%), Motivation (4.1%) and Quality (4.1%). These 7 constructs are responsible for 52.1% of the total mediators and moderators mentioned in the literature. The consequents most observed are Intention to revisit (14.3%), Loyalty (11.4%), Intention to visit (8.6%), Intention to buy wine (7.1%), willingness to recommend (7.1%) and Satisfaction (7.1%). The 6 most frequent consequent constructs are accountable for 55.7% of the total constructs. This research is innovative and valuable once identifies and analyzes the main theories and constructs studied in wine tourism field since 1997 to actuality, being helpful in guiding scholars to new streams of research, allowing the progress in wine tourism knowledge. From a managerial perspective it’s very valuable to wine tourism and marketing managers, as provides important insights related with constructs that have a direct impact in wineries strategy and business. With the findings of this systematic literature review we were able to present a framework to show the main constructs and relationships used to study WT, present literature gaps and point out avenues for future research, in addition to providing businesses some guidelines on best practices.